Processing Rumbia Starch Into Glucose Powder by Enzymatic Hydrolysis with Optimum Saccharification Temperature - Joan Nasya Alzena; Erwana Dewi; Robert Junaidi (Jurnal Teknologi, 2023)
Glucose powder is glucose in solid form which has the main component of glucose syrup obtained from starch hydrolysis, including sago from rumbia starch. As the population increases, it increases consumption of sugar as a sweetener for basic necessities such as food and drinks, the purposes of this research is identifying the optimum temperature for saccharification of the glucose powder produced from the enzyme hydrolysis process. This research used an enzyme hydrolysis process with the stages of gelatinization, liquification and saccharification for 72 hours with variations in temperature of 40°C, 50°C, 60°C and 70°C and obtained the optimum temperature results from these four temperatures. The optimal saccharification temperature is achieved by incubating at 50°C and 60°C with an incubation time of 72 hours or 3 days